Game-based learning and student motivation in digital classrooms - Helda; Hendra Nelva Saputra; Zila Razilu (Jurnal Inovasi dan Teknologi Pembelajaran, 2026)
The development of digital learning requires teachers to implement a learning model that not only delivers material but can also maintain students' attention and motivation to learn. Game-Based Learning (GBL) is a relevant approach because it integrates challenges, scores, live feedback, and interactive learning experiences. This study aims to analyse differences in student learning motivation before and after the implementation of GBL in digital classrooms at MTsN 1 Kendari. The research employed a quantitative approach with a quasi-experimental one-group pretest-posttest design. The research sample consisted of 102 students of digital classes who were selected using saturated sampling. The research instrument was in the form of a learning motivation questionnaire consisting of 19 statements and had a reliability of Cronbach's alpha of 0.871. Data were analysed using descriptive statistics, the Kolmogorov-Smirnov normality test, and a paired sample t-test. The results showed that the average learning motivation score increased from 24.4118 in the pretest to 25.9412 in the posttest. The t-test results showed a significant difference between the pretest and posttest scores, t(101) = -2,990; p = 0.004. The size of Cohen's dz effect of 0.296 suggests that the increase belonged the small category. These findings suggest that GBL has the potential to increase students' motivation to learn in the context of digital classrooms, although its practical impact still needs to be strengthened through a longer implementation and experimental design with control groups.